Optical behavior of MgO nanoparticles investigated using diffuse reflectance and near edge X-ray absorption spectroscopy - Singh, Jitendra Pal; Won, Sung Ok; Lim, Weon Cheol; Shim, Cheol-Hwee; Chae, Keun Hwa (ELSEVIER SCIENCE BV, 2017)
Present work investigates the optical behavior of MgO nanoparticles synthesized by using modified sol-gel method. Synthesized nanoparticles exhibit crystallite size in the range of 7-11 nm. Scanning and transmission electron microscopy show that particles are embedded in carboneous like template which is associated with low annealing temperature. These nanoparticles exhibit almost 10-20% reflectance in the UV-vis range which is almost 100% for bulk MgO. Near edge X-ray absorption spectroscopic measurements reflect that the optical response of these nanoparticles may be due to contribution from organic impurities. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: POROUS MGO; NANOBELTS; FACILE